Association between mortality and left ventricular ejection fraction in patients with Takotsubo Syndrome versus acute coronary syndrome - Abumayyaleh, Mohammad S. A.; El-Battrawy, Ibrahim; Kummer, Marvin; Gietzen, Thorsten; Behnes, Michael; Zhou, Xiao-Bo; Lang, Siegfried; Borggrefe, Martin; Akın, Ibrahim (In vivo, 2020)
Background/Aim: The association between ejection fraction (EF) and mortality in TTS patients as compared to ACS is limited. This study aims to investigate the association between EF and clinical outcomes in patients with TTS as compared to ACS. Patients and Methods: This study compared in-hospital, and long-term incidence of clinical outcomes for 5 years in patients with TTS and ACS. The study was composed of two groups EF≥35% and EF<35%. Results: The long-term mortality of the EF≥35% for 5 years was significantly higher in TTS patients as compared to ACS (18.1% vs. 7.7%, log-Rank; p<0.01). Irrespective of EF, a non-cardiovascular death was significantly higher in TTS as compared to ACS patients with EF≥35 (6.4% vs. 2.1%; p=0.02) and with EF<35% (21.4% vs. 7.5%; p=0.03). Conclusion: The long-term mortality is significantly higher in TTS as compared to ACS dominated by a non-cardiovascular cause of death at 5-years-follow-up.